Associative Ethical Dilemmas for Multicultural Sensitivity Assessment Derived from Adult Educational Theory - Keith B. Armstrong; Susan Timm (Adult Education Research Conference, 1999)
Adult educators promote non-formal assessment as demonstrated in their writings. Can tools then be developed that will gauge multicultural sensitivity? This paper examines that question, and personal, social, and legal implications of using multicultural sensitivity assessments for screening prospective employees, volunteers, and consultants for socially conscious groups, movements, and institutions.